Genetic algorithm for designation of safe ship trajectory - Mohamed-Seghir, M. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents a multi-stage decision-making process in the fuzzy environment, using a method based on genetic algorithm. Whose structure has been developed specifically for the problem of determining the optimal safe ship trajectory in collision situations, taking into account the provisions of the international law of the sea route with the International Maritime Organization convention on the International Regulations for Preventing Collisions at Sea (COLREGs).